Improving communication to increase uptake of high-risk breast cancer prevention appointments: Building a better letter - Evan K. Perrault; Maria K. Venetis; Tarah J. Ballinger (PEC Innovation)
Objective: Mailed letters to women identified as being at high-risk for developing breast cancer were not having the desired effect for encouraging appointments with prevention-focused providers at a large Midwest healthcare system. A partnership with communication scholars sought to revise the letter to increase awareness, intentions, and appointments. Methods: Guided by the Extended Parallel Process Model, survey responses were collected from letter recipients over the course of two years, both pre and post letter revision. Appointments attributed to letters were also tracked. Results: Recipients of the revised letter had increased knowledge regarding the length of prevention appointments and indicated greater self-efficacy and intentions to make and attend appointments compared to those who received the non-revised letter. A greater percentage who received the revised letter also made appointments. Conclusion: Partnering with communication scholars helped with improving a letter mailed to thousands of patients each year. Finding ways to increase response-efficacy of breast cancer prevention activities within communications may assist in increasing appointments. Innovation: Cross-disciplinary partnerships across the medical and social sciences – while not quick or simple – are essential for finding ways to improve patient wellbeing and hopefully reducing the prevalence of preventable diseases in the future.